2012
DOI: 10.1021/jp2095467
|View full text |Cite
|
Sign up to set email alerts
|

Equation of State of a Model Methane Clathrate Cage

Abstract: We investigate the behavior of a model methane clathrate cage under high hydrostatic pressures. The methane clathrate cage consists of 20 water molecules forming 12 pentagonal faces, with a methane molecule positioned at the cage center. The clathrate compound is located inside a fullerene-type arrangement of 180 He atoms to simulate an isotropic pressure. Different pressures are simulated by decreasing the radius of the He array. The minimal energy of the total system for each configuration is calculated by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…These studies were restricted to use less than a dozen atoms in the building of the unit cell because the computational cost of the ab initio methods gives little chance to explore alternative arrangements with different numbers of atoms that could lead to other geometries in the conformation of the unit cell. In this regard, similar investigations have been carried out using hydrogen clusters, the finite-size counterpart of crystals, and for other systems of energetic interest . In particular, it was shown that hydrogen molecules are capable of self-assemblimg, leading to stable clusters with geometries that depend of both the number of hydrogen molecules and the thermodynamic conditions of pressure and temperature .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…These studies were restricted to use less than a dozen atoms in the building of the unit cell because the computational cost of the ab initio methods gives little chance to explore alternative arrangements with different numbers of atoms that could lead to other geometries in the conformation of the unit cell. In this regard, similar investigations have been carried out using hydrogen clusters, the finite-size counterpart of crystals, and for other systems of energetic interest . In particular, it was shown that hydrogen molecules are capable of self-assemblimg, leading to stable clusters with geometries that depend of both the number of hydrogen molecules and the thermodynamic conditions of pressure and temperature .…”
Section: Introductionmentioning
confidence: 88%
“…We pay attention to their structural and electronic properties by comparing with the isoelectronic and stable cluster H 26 , constituted by hydrogen solely, with the extra H 2 particle replacing He and Li + . The expressions that determine the pressure and volume from the basic mechanical variables of position, velocity, and force are discussed briefly; nevertheless, they have been discussed a number of times and can be found elsewhere …”
Section: Encapsulation Model and Methodsmentioning
confidence: 99%
“…Furthermore, only one other first-principles theoretical study exists on the mechanical and thermal properties of sII gas hydrates. First-principles modeling has been successfully implemented in many previous gas hydrate studies. These methods provide the benefit of a thoroughly controlled environment, eliminating impurities and structural defects, where an in-depth investigation into the properties and structure of gas hydrates at the atomistic scale is facilitated. The goal of this paper is to fill the aforementioned gaps in hydrate literature by presenting the elastic and acoustic properties of several sII gas hydrates from hydrocarbon formers (i.e., methane, ethane, propane, and isobutane), using first-principles simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Then, by following standard rules of analytical mechanics, the Lagrangian equations of motion are obtained. The model provides a formal framework for the previous studies of the hydrogen gas under the effects of pressure and temperature [4][5][6][7][8][9][10][11]. Contrary to other proposed models, the present model includes a representation of the medium surrounding the system of the confined particles by a direct inclusion of such properties as the structure and rigidity of the container, the viscosity of the fluid forming the surrounding medium, etc., described in terms of mechanical and statistical mechanics axioms.…”
Section: Introductionmentioning
confidence: 99%